Hubungan Tingkat Pengetahuan Masyarkat Terhadap Penggunaan Antibiotik Di Kelurahan Alalak Utara - Shofia Rahmi; Darini Kurniawati; Nurul Hidayah (LPPM Universitas Sari Mulia, 2020)
Background: Antibiotics are drugs that used to treat infections. Irrational use of antibiotics can increase the incidence of bacterial resistance. The proper use of antibiotics is influenced by several factors, one of the factors is knowledge. Objective: Analyze the relationship between the level of society knowledge and rational use of antibiotics in the North Alalak Village. Methods: This research used observational analytics design (non-experimental) and cross – sectional study design. The population are adult communities with ages around 20-60 years in North Alalak Village. The researcher take 45 people as sample by using purposive sampling. Measure tools or instrument that the researcher used is validated questionnaire. Data was analyzed by using Spearman Rho with 95% level of confidence. Results: The results of the respondents knowledge level in good categories were 4 people (8.9%), quite were 25 people (55.6%) and less were 16 people (35.6%). The results of using antibiotics rationally by respondents were 3 people (6.7%) and irrationally by 42 people (93.3%). The prevalence ratio (PR) value obtained was 20.83 and the Spearman rho test results obtained were a significance value of 0.014 (<0.05), a correlation coefficient of 0.364 and a positive correlation direction. There is a correlation between the level of knowledge and the use of antibiotics in the society in North Alalak village. Conclusion: Knowledge about antibiotics is related to rational antibiotic use. People needs to add more information about rational use of antibiotics with counseling guidance, seminars and other information.